COMPANY SIZE MEDIATES THE RELATIONSHIP BETWEEN PROFITABILITY AND EARNINGS MANAGEMENT IN PHARMACEUTICAL INDUSTRY COMPANIES LISTED ON THE INDONESIAN STOCK EXCHANGE FROM 2019 TO 2023 - Balo, Augustinus (Universitas Dharmawangsa Medan, 2025)
The research method uses a crucial quantitative approach. The objective is to analyze the effect of profitability on the size of a company's earnings management, as well as its role as a mediating variable in the relationship between profitability and earnings management in pharmaceutical companies listed on the Indonesia Stock Exchange (IDX) for the 2019–2023 period. The study population includes 13 pharmaceutical sub-sector companies, with a sample of 6 companies. Secondary data were obtained from the IDX, OJK, and BPS, then analyzed using the PLS method to statistically test the relationship between variables. The research results are: 1) Profitability does not significantly influence company size because profit fluctuations during the pandemic were more influenced by market conditions and short-term drug demand, rather than asset expansion. Furthermore, pharmaceutical companies allocate more profits to R&D or dividend payments, rather than adding fixed assets. 2) Large companies tend to engage in earnings management due to public pressure, operational complexity, and greater accounting and financing flexibility. 3) The company is not a primary factor driving earnings management; profitability does not significantly influence earnings management practices. 4) The influence of profitability on earnings management practices is more influenced by factors other than company size, such as managerial policies, ownership structure, and external pressures.